Summer mortality of hatchery-produced Pacific oyster spat (Crassostrea gigas). II. Response to selection for survival and its influence on growth and yield - Degremont, Lionel; Bedier, Edouard; Boudry, Pierre (Aquaculture, 2010)
Response to divergent selection for "high" and "low" survival during the summer period, from July to October, was investigated in juvenile (six-month-old) Pacific oysters, Crassostrea gigas, by producing two sets of progenies in 2002 (Generation 2) and three sets of progenies in 2003 (Generation 3). A strict between-family approach was used and resistance of these selected progenies to summer mortality was assessed in three sites along French coasts, to determine their response to selection and estimate realized heritability of the trait. A significant difference in survival was observed between the "high" and "low" selected groups at all sites for all sets of progenies, indicating a significant genetic component. High realized heritabilities for survival obtained from Generation 2 oysters, ranging from 0.61 ± 0.08 to 0.98 ± 0.15, were in line with previous results from the first generation. Finally, Generation 3 realized heritability, ranging from 0.55 ± 0.18 to 0.81 ± 0.13, supported results from Generation 2. Our results demonstrate that selective breeding to improve survival during the first summer can be successfully implemented and should lead to rapid gains. Overall, selection on survival did not have any impact on growth, although it did have one on yield.